A calix[4]arene with diethylthiocarbamoylmethyloxy substituents in the 1,3 positions - Drew, M; Beer, P; Ogden, M (1997)
The title compound 5,11,17,23-tetra-tert-butyl-N,N,-N′,N′-tetraethyl-26,28- dihydroxypentacyclo[19.3.1.13,7.-19,13.1 15,19]octacosa-1(25),3,5,7(26),9,11,13(27),15,17,-19(28),21,23- dodecaene-25,27-diylbis(oxythioacetamide), C56H78N2O4S2, was synthesized from the reaction of the known 1,3-bis(diethylamide)-substituted calix[4]-arene with 2,4-bis(4-methoxyphenyl)-1,3-dithia-2,4-diphosphetane-2,4-disulfide (Lawesson's reagent). The calixarene is found to have a pinched-cone conformation, with no solvent molecule in the cavity.